Antioxidant, Pancreatic Lipase Inhibitory, and Tyrosinase Inhibitory Activities of Extracts of the Invasive Plant Spartina anglica (Cord-Grass) - Geum Jin Kim; Songhee Park; Eonmi Kim; Hyukbean Kwon; Hae-Jin Park; Joo-Won Nam; Seong-Soo Roh; Hyukjae Choi (MDPI AG, 2021)
Since 2016, the invasive halophyte Spartina anglica has been colonizing mudflats along the western coast of South Korea. In order to minimize costs on S. anglica expansion management and waste-treatment of collected biomass, the potential application of the collected biomass of S. anglica was investigated. Ethanolic extracts and subfractions thereof (hexanes, methylene chloride, ethyl acetate, 1-butanol, and water-soluble) of the aerial and belowground parts of S. anglica showed free radical-scavenging [2,2-diphenyl-1-picrylhydrazyl (DPPH), and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS)], tyrosinase inhibitory, and pancreatic lipase inhibitory activities. An ethyl acetate fraction derived from aerial parts (EA-a) showed the most potent radical-scavenging and pancreatic lipase inhibitory activities, whereas tyrosinase inhibition was mainly observed in the methylene chloride soluble fractions (MC-bg) and other lipophilic fractions (ethyl acetate and hexanes layers) obtained from belowground parts. The major EA-a compound isolated and identified was 1,3-di-O-trans-feruloyl quinic acid (1) based on spectroscopic analysis, whereas the two major MC-bg compounds were identified as p-hydroxybenzaldehyde (2) and N-trans-feruloyltyramine (3). Compounds 1 and 3 scavenged both DPPH and ABTS radicals, whereas 1 and 2 inhibited pancreatic lipase activity. These results indicate that extracts and fractions of S. anglica have antioxidant, anti-obesity, and whitening properties with potential pharmaceutical, cosmeceutical, and functional food applications.